Correlation between Individual Characteristics, Work Monotony, and Mental Workload with Work Stress - Ainayya Rizky Savitri; Noeroel Widajati (Universitas Airlangga, 2023)
Introduction: Work stress is the inability of a worker to face job demands, leading to discomfort while working. Work stress can be caused by many factors, among them work monotony, excessive workload, and individual characteristics. This study's aim was to analyze the strength of the relationship among individual characteristics, work monotony, and mental workload with work stress on the crane operators of Jamrud Terminal. Methods: This study used cross-sectional design. The population in this study was all crane operators in Jamrud Terminal as many as 28 people. Total sampling was applied as sampling technique. The independent variables in this study include individual characteristics (age and tenure), work monotony obtained from the questionnaire, mental workload which was appraised using NASA-TLX questionnaire, while the dependent variable was work stress assessed with DASS 42 questionnaire. Coefficient contingency and Spearman correlation test were applied to analyze collected data. Results: This study revealed 13 operators (46.4%) felt normal work stress and the other operators (53.6%) felt work stress ranging from light until very heavy. Contingency coefficient correlation test resulted in weak relationship among age and work stress and strong relationship among work monotony and work stress. Spearman correlation test revealed weak relationship among tenure and work stress and moderate relationship among mental workload and work stress. Conclusion: There were relationships among work monotony and mental workload with work stress on crane operators. The company is advised to give work music, variation on work, and arrange proper break time for crane operator.